Short communication: Evaluation of bulk tank milk microbiological quality of nine dairy farms in Tennessee - Gillespie B. (2017)
The purpose of this study was to evaluate the bulk tank milk (BTM) quality of 9 East Tennessee dairy farms and to determine its relationship with selected quality milk parameters. Bulk tank milk samples (n = 1,141) were collected over a 42-mo period (June 2006 through November 2009) from farms, based on their preliminary incubation count (PIC) history. Parameters of BTM quality evaluated in this study included somatic cell count (SCC), standard plate count (SPC), PIC, laboratory pasteurization count (LPC), Staphylococcus spp. count, Streptococcus spp. count, and coliform count. Strong correlations between SPC and Streptococcus spp. counts (0.72) and between SPC and PIC (0.70) were found. However, moderate correlations were seen among other milk quality parameters. In addition, seasonal variations for some milk quality parameters were noted. For example, milk quality parameters such as SCC, SPC, LPC, and coliform count were significantly higher in summer, whereas Streptococcus spp. counts were significantly higher in winter. No seasonal variation in PIC or Staphylococcus spp. counts was observed. Summarizing, results from this investigation showed the importance of using several bacterial counts (SCC, SPC, PIC, LPC, Streptococcus spp. count, Staphylococcus spp. count, and coliform counts) as simultaneous indicators of milk quality. © 2012 American Dairy Science Association.